GROWTH OF PERFORMANCE SILVER POMPANO FISH FRY, Trachinotus blocii (LACEPEDE) CULTURED IN THE NET CAGE AT THE POND - Tony Setiadharma; Gigih Setia Wibawa; Irwan Setiadi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
Silver pompano fish is a prospective commodity that can be cultured and contains high economic value. Due to its high economic value nationally and internationally, it is important to develop nursery business. The silver pompano fish nursery conducted in a pond become efficient because it can be easily controlled. The purpose of the study was to know the technology and growth of silver pompano fish fry in cages at a pond. Research activities were carried out in the hafa size (3x3x1m3) in ponds. The seeds were taken from hatchery with size of 5.0-6.0 cm. Stocking density of seeds were 50 pc/ m³. The nursery were reared for 90 days till the fry reached their size in between 15.0 and 18.0 cm. The commercial pellets with protein content of 28-30% with dose of 5-8% of body weight were provided in the morning and afternoon at satiation. Sampling of fry was conducted every 30 days, to measure the survival rate (SR), total length (TL) and body weight (BW). Data were processed with descriptive analysis. The results showed that the survival rate was 90.20 ± 2.60 %, total length was 16.80± 2.70 cm, and body weight was 145.20 ± 2.70 g. The diversity of fry has four size categories i.e., large (L), medium (M), small (S), and super small (SS) with percentage average of 17.50%, 52.70%, 20.70% and 9.10%, respectively. Keywords: net cage, pond, silver pompano fish, growth, survival